2007
DOI: 10.1038/sj.mt.6300167
|View full text |Cite
|
Sign up to set email alerts
|

Role of Acid Ceramidase in Resistance to FasL: Therapeutic Approaches Based on Acid Ceramidase Inhibitors and FasL Gene Therapy

Abstract: Head and neck squamous cell cancers (HNSCC) are particularly aggressive and are resistant to many forms of treatment. Ceramide metabolism has been shown to play an important role in cancer progression and cancer resistance to therapy in many tumor models, including HNSCC. Here, we study the role of the ceramide-metabolizing enzyme acid ceramidase (AC) in therapeutic responses in HNSCC. First, we show that AC is over-expressed in 70% of head and neck squamous cell tumors compared with normal tissues, suggesting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
70
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 85 publications
(72 citation statements)
references
References 21 publications
1
70
1
Order By: Relevance
“…44,45 Furthermore, acid ceramidase inhibitors such as LCL204 are also being studied as new cancer therapies. 46 Since BEX2 has a significant effect on the survival and growth of breast cancer cells, such as their sensitivity to proapoptotic agents and the regulation of PP2A activity in these cells, BEX2 is a potential therapeutic target in breast cancer.…”
Section: Cancer Cell Biologymentioning
confidence: 99%
“…44,45 Furthermore, acid ceramidase inhibitors such as LCL204 are also being studied as new cancer therapies. 46 Since BEX2 has a significant effect on the survival and growth of breast cancer cells, such as their sensitivity to proapoptotic agents and the regulation of PP2A activity in these cells, BEX2 is a potential therapeutic target in breast cancer.…”
Section: Cancer Cell Biologymentioning
confidence: 99%
“…While the characterization of aberrant, cancer-associated gene expression in tissues obtained for diagnosis versus noncancerous tissues is a prominent arena of research (39), the response of tumors to therapy also represents a critical avenue of investigation (22). Work by this group and others has demonstrated that the ceramide-metabolizing enzyme, acid ceramidase (AC), can play an important role in resistance to anticancer therapies (40)(41)(42)(43)(44)(45)(46)(47), including IR (26,36,48,49). In this report, we evaluated transcriptional activation of AC in PCa cells treated with radiation.…”
Section: Introductionmentioning
confidence: 99%
“…Because Cer hydrolysis is the major pathway for SPH generation (45), ASAH1 plays a key role in regulating cellular homeostasis by controlling the Cer/SPH/S1P balance within the cell. In addition, the aberrant expression of ASAH1 in various human cancers (46 -49), including breast cancer (50), prompted the emergence of this enzyme as a potential target for chemotherapy (48,51,52). Inhibitors of ASAH1 such as B13 and LCL464 were shown to cause Cer accumulation and prevent tumor growth (51,53).…”
mentioning
confidence: 99%